A small-molecule organic semiconductor - Yakuphanoğlu, Fahrettin; Aydin, M; Arsu, N; Sekerci, M (Amer Inst Physics, 2004)
The electrical conductivity and optical properties of bis-diethylaminokumarin have been investigated. The electrical conductivity of the compound exhibited three-dimensional hopping conduction in the temperature range 295-321 K. The compound shows a typical semiconductor property, and its semiconducting property results from delocalization of the pi-electrons in the structure. To determine the optical band gap of the compound, an optical absorption study was made in the wavelength range 250-600 nm. The optical study revealed that the optical transition is the allowed indirect one. The electronic parameters, such as the electrical conductivity at room temperature sigma(25), activation energy E, and optical band gap E-g of the compound are 1.46 x 10(-5) S/cm, 0.42 eV, and 2.46 eV, respectively. These values are in agreement with electronic parameters of organic semiconductors. (C) 2004 MAIK Nauka/Interperiodica.